2015
DOI: 10.1093/rheumatology/keu451
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine reduces risk of incident diabetes mellitus in lupus patients in a dose-dependent manner: a population-based cohort study

Abstract: In SLE patients, the use of HCQ is associated with reduced risk of incident diabetes mellitus in a dose-dependent manner. High-dose glucocorticoids increase the risk of diabetes, which can be decreased by concomitant HCQ use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 20 publications
4
94
1
3
Order By: Relevance
“…This suggests that PRED may exacerbate the early insulin response to nutrient load, thus potentially worsening IR and the predisposition to long-term b cell dysfunction. In contrast to PRED, HCQ has been associated with lower levels of fasting glucose and HOMA IR and a reduced risk of type 2 DM in SLE patients (39). We did not observe any association between HCQ use and insulin sensitivity estimates.…”
contrasting
confidence: 79%
“…This suggests that PRED may exacerbate the early insulin response to nutrient load, thus potentially worsening IR and the predisposition to long-term b cell dysfunction. In contrast to PRED, HCQ has been associated with lower levels of fasting glucose and HOMA IR and a reduced risk of type 2 DM in SLE patients (39). We did not observe any association between HCQ use and insulin sensitivity estimates.…”
contrasting
confidence: 79%
“…The precise anti-inflammatory mechanism of HCQ is not known and is probably related to alkalinization of endosomal organelles in immune cells. HCQ has been shown to reduce the incidence of diabetes among patients with rheumatoid arthritis and lupus and to improve glycemia in patients with rheumatic disorders and diabetes (102,103). Animal studies have shown that antimalarials improve insulin secretion and peripheral insulin sensitivity in diabetic rats (104).…”
Section: Salsalatementioning
confidence: 99%
“…As the reduction in FBG, PPBG were 8%, 6.5 % respectively therefore, this meant a significant difference between the patients before and after using HCQ therapy [29,33]. Plasma levels of fasting insulin, glucose and lipids were measured in a certain number of Finally, like many studies, SLE patients and showed higher plasma levels in insulin, TC, LDL, TG, and lower levels in HDL than control subjects.…”
Section: Discussionmentioning
confidence: 91%